ANALISIS PENGELOLAAN KEUANGAN PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KELURAHAN MATANI KECAMATAN TOMOHON TENGAH KOTA TOMOHON - Syella Vebria Awuy; Gilly Marlya Tiwow; Silvana Shirly Alice Oroh (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Background: MSMEs provide an essential economic function for Tomohon City. However, expansion and access to formal finance are sometimes impeded by inadequate financial management practices. The objectives of this research are to examine the financial management practices of MSMEs in Matani Satu, Matani Dua, and Matani Tiga, to determine the factors that help or hinder these practices, and to assess the degree to which these businesses understand (SAK EMKM). Procedures for doing research: With the use of basic quantitative data analysis, this research takes a descriptive qualitative method. Ten (MSMEs) were chosen at random for in-depth interviews and surveys. The data was analyzed by comparing the results from the field with theories and empirical studies of financial management that have been published within the last five years. Outcome also Discussion: research outcome assumed financial management practices of MSMEs in Central Tomohon are at a subsistence level, characterized by the phenomenon of mixing funds acknowledged by 90% of respondents, as well as manual and reactive recording. The main inhibiting factords are low financial literacy and a knowledge – action gap, where awareness of the importance of record-keeping is not matched by technical skills and time. This gap is exacerbated by the very limited reach of local government intervention (only 10% of respondents have participated I training). The fatal consequence is a zero percent (0%) implementation rate of the MSME Financial Accounting Standards (SAK), resulting in 80% of MSME loan applications being rejected due to the inability to present credible financial reports. ABSTRAK Latar Belakang: UMKM berfungsi besar guna perekonomian Kota Tomohon. Namun praktik Pengelolaan Keuangan yang buruk sering menjadi hambatan utama pertumbuhan dan akses permodalan formal. Penelitian ini bertujuan menganalisis praktik pengelolaan keuangan mengidentifikasi factor penghambat dan pendukung, serta mengukur Tingkat pemahaman UMKM pada SAK EMKM Kelurahan Matani Satu, Matani Dua, dan Matani Tiga. Metode: studi mempergunakan desain deskriptif kualitatif beserta pengkajian data kuantitatif sederhana. Data dikumpulkan melalui survey dan wawancara mendalam terhadap 10 pelaku UMKM ditetapkan purposive sampling. Pengkajian data dilaksanakan menyandingkan temuan lapangan dengan teori pengelolaan keuangan dan studi empiris lima tahun terakhir. Hasil dan pembahasan: Temuan studi memperlihatkan praktik pengelolaan keuangan UMKM di Tomohon Tengah berada pada Tingkat subsitensi, ditandai oleh fenomena pencampuran dan (mixing funds) yang diakui oleh 90% responden, serta pencatatan yang bersifat manual dan reaktif. Faktor penghambat utama Adalah Literasi Keuangan yang Rendah dan Kesenjangan Aksi (Knowlegde-Action Gap), Dimana kesadaran akan pentingnya pencatatan tidak diimbangi dengan kemampuan teknis dan waktu Kesenjangan ini diperparah oleh jangkauan intervensi Pemerintah Daerah yang sangat terbatas (hanya 10% responden pernah ikut pelatihan). Konsekuensi fatalnya adalah Tingkat implementasi SAK EMKM nol persen (0%), yang menyebabkan 80% permohonan kredit UMKM ditolak karena tidak mampu menyajikan laporan keuangan yang kredibel.